Comparison of different auxiliary techniques used during root canal filling removal in terms of the amount of apically extruded debris: In vitro study - Ismail Uzun; Kevser Şenel; Rawan Alqawasmi (PLoS ONE, 2025)
Background One of the main challenges in endodontic retreatment is managing apical debris extrusion, which can influence both healing and patient comfort. Different retreatment methods result in varying levels of extrusion. This study aims to quantitatively compare the extent of apical debris extrusion caused by different auxiliary techniques during the extraction of root canal fillings in mandibular molars, to help guide the selection of an optimal endodontic approach. Materials and methods Sixty mandibular molar teeth scheduled for extraction due to periodontal reasons, such as advanced bone loss and periodontal disease, which rendered them non-restorable, were collected. All extractions were performed with prior informed consent from the patients, ensuring adherence to ethical standards. Preparation was performed with the Protaper Next file system, focusing on X3 files according to the manufacturer’s guidelines. Teeth were filled using the lateral compaction technique with AH Plus sealer and stored at 100% humidity at 37°C for two weeks for the sealant to set. The samples were divided into four groups (n = 15 each): Protaper Universal Retreatment (PTUR), Ultrasonic + PTUR, Orange Oil + PTUR, and System B + PTUR, with PTUR procedural steps followed to attain working length. During preparation, 15 ml of distilled water was used, followed by 1 ml of distilled water for debris collection post-procedure. The debris was incubated at 68°C for five days to evaporate the water, and tube weights were recorded and compared statistically across groups. Results The study assessed debris extrusion during endodontic retreatment. The PTUR group showed the least extrusion (average 1.1 mg, SD ± 1.05 mg), indicating a more controlled approach. The Ultrasonic + PTUR group exhibited higher extrusion (average 4.2 mg, SD ± 2.12 mg), reflecting a more invasive technique with a greater potential for debris extrusion. The Orange Oil + PTUR group displayed moderate extrusion levels (average 2.5 mg SD ± 1.46 mg), reflecting the solvent’s effect. The System B + PTUR group had the highest extrusion (average 4.3 mg, SD ± 1.87 mg), indicating it as the method associated with the greatest debris displacement. Statistically significant differences were found between the PTUR group and the other groups (P < 0.05). Additionally, a significant difference was observed between the Orange Oil + PTUR group and both the Ultrasonic + PTUR and System B + PTUR groups (P < 0.05). No significant difference was noted between the System B + PTUR and Ultrasonic + PTUR groups (P > 0.05). Conclusion The study concludes that auxiliary methods used during root canal filling removal significantly impact the degree of apical debris extrusion, with some methods leading to greater extrusion than others.